Manifesto on small airway involvement and management in asthma and chronic obstructive pulmonary disease: an Interasma (Global Asthma Association - GAA) and World Allergy Organization (WAO) document endorsed by Allergic Rhinitis and its Impact on Asthma (ARIA) and Global Allergy and Asthma European Network (GA2LEN) - F. Braido; N. Scichilone; F. Lavorini; O.S. Usmani; L. Dubuske; L.P. Boulet; R. Mosges; C. Nunes; M. Sanchez-Borges; I.J. Ansotegui; M. Ebisawa; F. Levi-Schaffer; et al. (World Allergy Organization Journal, 2016)
Evidence that enables us to identify, assess, and access the small airways in asthma and chronic obstructive pulmonary disease (COPD) has led INTERASMA (Global Asthma Association) and WAO to take a position on the role of the small airways in these diseases.Starting from an extensive literature review, both organizations developed, discussed, and approved the manifesto, which was subsequently approved and endorsed by the chairs of ARIA and GA2LEN. The manifesto describes the evidence gathered to date and defines and proposes issues on small airway involvement and management in asthma and COPD with the aim of challenging assumptions, fostering commitment, and bringing about change.The small airways (defined as those with an internal diameter <2 mm) are involved in the pathogenesis of asthma and COPD and are the major determinant of airflow obstruction in these diseases. Various tests are available for the assessment of the small airways, and their results must be integrated to confirm a diagnosis of small airway dysfunction.In asthma and COPD, the small airways play a key role in attempts to achieve disease control and better outcomes. Small-particle inhaled formulations (defined as those that, owing to their size [usually <2 μm], ensure more extensive deposition in the lung periphery than large molecules) have proved beneficial in patients with asthma and COPD, especially those in whom small airway involvement is predominant.Functional and biological tools capable of accurately assessing the lung periphery and more intensive use of currently available tools are necessary. In patients with suspected COPD or asthma, small airway involvement must be assessed using currently available tools. In patients with subotpimal disease control and/or functional or biological signs of disease activity, the role of small airway involvement should be assessed and treatment tailored. Therefore, the choice between large- and small-particle inhaled formulations must reflect the physician’s considerations of disease features, phenotype, and response to previous therapy. This article is being co-published in Asthma Research and Practice and the World Allergy Organization Journal.